Gulf women - Sonbol, Amira El Azhary (Hamad bin Khalifa University Press, 2012)
This groundbreaking collection of essays provides a greater understanding of the history of the Gulf and the Arab world and is of relevance to Muslim women everywhere. Featuring research never published before, Gulf Women is the result of a project aimed at finding sources and studying the history of women in the region. The chapters cover ancient history and the medieval, early modern, and contemporary periods. Presenting discourses on the life of women in early Islam, women's work and the diversity of their economic contribution, the family-and how it changed over time-as well as the legal system and laws dealing with women and family from the pre-modern to the modern periods, this is a pioneering collection by leading scholars from Arab and international universities.